2019
DOI: 10.1016/j.yjmcc.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tracheal gene delivery of aerosolized SERCA2a to the lung suppresses ventricular arrhythmias in a model of pulmonary arterial hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) results in right ventricular (RV) failure, electro-mechanical dysfunction and heightened risk of sudden cardiac death (SCD), although exact mechanisms and predisposing factors remain unclear. Because impaired chronotropic response to exercise is a strong predictor of early mortality in patients with PAH, we hypothesized that progressive elevation in heart rate can unmask ventricular tachyarrhythmias (VT) in a rodent model of monocrotaline (MCT)-induced PAH. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In the prevention protocol, a single intratracheal injection of aerosolized AAV1.SERCA2a prevented PAH in the MCT‑injected rats [ 198 ]. Furthermore, aerosolized AAV1.SERCA2a gene transfer improved myocardial electrophysiological remodeling and ventricular tachyarrhythmia’s susceptibility, indicating the efficacy of SERCA2a non‑cardiac gene therapy approach for arrhythmia suppression [ 297 ]. Nebulization of AAV1.SERCA2a, which is a Yukatan miniature swine model of chronic PH, resulted in attenuation of pulmonary vascular resistance, and a trend towards better long-term survival compared to control animals [ 298 ].…”
Section: Gene‑delivery Approaches and Gene Therapymentioning
confidence: 99%
“…In the prevention protocol, a single intratracheal injection of aerosolized AAV1.SERCA2a prevented PAH in the MCT‑injected rats [ 198 ]. Furthermore, aerosolized AAV1.SERCA2a gene transfer improved myocardial electrophysiological remodeling and ventricular tachyarrhythmia’s susceptibility, indicating the efficacy of SERCA2a non‑cardiac gene therapy approach for arrhythmia suppression [ 297 ]. Nebulization of AAV1.SERCA2a, which is a Yukatan miniature swine model of chronic PH, resulted in attenuation of pulmonary vascular resistance, and a trend towards better long-term survival compared to control animals [ 298 ].…”
Section: Gene‑delivery Approaches and Gene Therapymentioning
confidence: 99%
“…The pathophysiologic mechanisms of right ventricular remodelling and dysfunction include calcium overload [ 71 ], oxidative stress injury and cardiomyocyte apoptosis [ 72 , 73 ]. Ang-(1–7) supplementation can slow down the development of right ventricular dysfunction and improve the maximum rate of right ventricular pressure rise during the isovolumic systolic period [ 74 , 75 ].…”
Section: The Role Of the Ace2-ang-(1–7)-mas Axis In Pahmentioning
confidence: 99%
“…Furthermore, several studies have previously demonstrated that SERCA2a gene transfer via intra-tracheal delivery of aerosolized adeno-associated virus serotype 1 (AAV1) carrying the human SERCA2a gene (AAV1.SERCA2a) inhibits PAH in the MCT-induced PH rat model and chronic post-capillary pulmonary hypertension in a large animal model ( Aguero et al, 2016 ; Hadri et al, 2013 ). In the MCT-induced PAH, gene transfer of SERCA2a via intratracheal delivery of AAV1.SERCA2a decreased RVSP, pulmonary artery pressure (PAP), vascular remodeling, right ventricular hypertrophy (Fulton Index), and RV fibrosis in comparison with MCT-PH rats treated with a control AAV1 carrying β-galactosidase or saline ( Strauss et al, 2019 ). In a prevention protocol, AAV1.SERCA2a delivery attenuated adverse hemodynamic profiles as well as indices of pulmonary and cardiac remodeling in comparison with rats administered with AAV1 carrying β-galactosidase or saline.…”
Section: Emerging Therapiesmentioning
confidence: 99%